The development of mini gantry - Mohd Azli Mohammad Bahrun (School of Electrical System Engineering, University Malaysia Perlis, 2011)
The mini gantry is often used in small industries and big industries. For example, the electronics industry and raise the container port industry. It is used for workers to work conveniently to move the loads from one place to another place. The main advantage of mini gantry is it can reduce workers energy consumption because the mini gantry can help to lift the heavy and smalls load quickly and intelligently. Besides that, the mini gantry can improve the work safety and reducing labors. The project is divided into two main parts which are hardware part and software part. The hardware components comprise of aluminums plate, sprocket, chains, ropes, and bearing. The software tools are the Programmable Integrated Control (PIC) 16F877 microcontroller type, Liquid Crystal Display (LCD) screen, sensor infrared distance, power supply 12V, direct current (DC) motor and limit switch. The main feature in this project is using PIC micro-controller for small gantry 2-dof. The program used in PIC 16F877 microcontroller is C program. The position calculations of gantry mechanism have been performed. Then, the actual measurements of positions and angle input parameters are compared. Further calculations are performed to generate the input shape commands to reduce unbalanced vibrations. The development of mini gantry using PIC Microcontroller was successfully implemented and provides principal knowledge about the mini gantry operation at several conditions of industries.